Pengaruh Influencer Marketing dan Brand Awareness Terhadapa Keputusan Pembelian Street Boba - Kelvin Yohanes (2021)
This research is using a descriptive quantitative study that aims to see and analyze the influence of Influencer Marketing and Brand Awareness on Street Boba Purchase Decisions. The sample selection technique in this study used a non-probability sampling technique so that the entire population was used as a sample using the Lemeshow calculation formula and obtained a sample of 100 respondents. Smart PLS 3.0 Software and Microsoft Office Excel software are used on the Hypothesis testing. The results obtained from the examiners are (1) There is a significant effect of Influencer Marketing on Purchase Decisions, (2) There is a significant effect of Brand Awareness on Purchase Decisions.